J. M. Roldán, J. M. Blázquez y A. del Castillo, Historia de Roma. Tomo II: El Imperio romano (siglos I-III), Madrid, Ed. Cátedra, 1989, 562 pp - Montero, Santiago (Gerión. Revista de Historia Antigua, 1991)
Sin resumen